The Pine Branch, February 1922 - (:unkn) unknown (Valdosta, Ga. : Writers Club of the South Georgia State Normal College., 1922)
The Pine Branch. Periodical magazine. Created and published by the Writers Club of the Georgia State Womans College, Valdosta, Georgia. Includes: editorials, photographs, poems, short stories, and other writings.
On the Ninth Anniversary of S. G. S. N. C P Mary Ethel Moses; Frances Dekle; Estelle Barker; Mary Poindexter; Verna Scarborougs; Edna Roberson; Sally Kate Wolfe; Birdie VanBrackle; Leo Prine; Eppie Robertson; Madeline Culbreth; Page 1 | Valentine and a Haircut Page 2 | Three Maids and a Male Person Page 6 | Thrills Subdued Page 9 | Bidding the Home Boys Farewell Page 10 | Editorial Page 12 | Twigs Page 14 | Locals Page 15 | Alumnae Page 17 | Society Notes Page 18 | Humorous Page 20 |
Keywords: College publications; College student newspapers and periodicals; Valdosta State University--Periodicals; Women; Women's colleges--Georgia--Valdosta; South Georgia State Normal College; Valdosta; Schools--Georgia; Education